Infeksi Herpes Simpleks Dalam Kehamilan - Fauzia Andrini Djojosugito (Fakultas Kedokteran Universitas Riau, 2016)
Herpes simplex virus is one the most common causes of sexually transmitted diseases. This infection is common inreproductive age women and can cause severe sequealae for fetus and neonates because this virus can be transmittedto the fetus during pregnancy and the newborn. Infection of Herpes simplex can occurs as first or primary infectionand recurrent infection. Most of the case is asymptomatic. Rarely during intrauterine, the risk of transmission ofmaternal-fetal can be increased during the last trimester of pregnancy and delivery. Based on type of infection,primary or recurrent, performing a treatment with antiviral drugs or caesarean section delivery can decrease the riskof neonatal infection